2001
DOI: 10.1038/82881
|View full text |Cite
|
Sign up to set email alerts
|

Spinal axon regeneration evoked by replacing two growth cone proteins in adult neurons

Abstract: In contrast to peripheral nerves, damaged axons in the mammalian brain and spinal cord rarely regenerate. Peripheral nerve injury stimulates neuronal expression of many genes that are not generally induced by CNS lesions, but it is not known which of these genes are required for regeneration. Here we show that co-expressing two major growth cone proteins, GAP-43 and CAP-23, can elicit long axon extension by adult dorsal root ganglion (DRG) neurons in vitro. Moreover, this expression triggers a 60-fold increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
234
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(243 citation statements)
references
References 51 publications
(85 reference statements)
8
234
0
1
Order By: Relevance
“…This occurs when COS-7 cells, which do not express GAP-43, are transfected with a constitutively active form of cdc42 [34]. Consistent with this idea, the effects of GAP-43 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and constitutively active cdc42 together are additive [34]. Since the first 14 residues of GAP-43 do not contain the protein kinase C phosphorylation site, it was suggested that interaction of only the first 14 residues with membranes is sufficient to Fig.…”
Section: Gap-43 G Proteins Small Gtpases and Filopodiasupporting
confidence: 57%
See 1 more Smart Citation
“…This occurs when COS-7 cells, which do not express GAP-43, are transfected with a constitutively active form of cdc42 [34]. Consistent with this idea, the effects of GAP-43 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and constitutively active cdc42 together are additive [34]. Since the first 14 residues of GAP-43 do not contain the protein kinase C phosphorylation site, it was suggested that interaction of only the first 14 residues with membranes is sufficient to Fig.…”
Section: Gap-43 G Proteins Small Gtpases and Filopodiasupporting
confidence: 57%
“…This suggests that signals must be transduced from particular extracellular molecules to GAP-43 in order for neurite outgrowth to occur. Overexpression of GAP-43 and CAP-23 in dorsal root ganglion neurons increased axon growth in vitro and in the injured spinal cord [10].…”
Section: Gap-43 Neurotrophins Cell Adhesion Molecules Developmentmentioning
confidence: 99%
“…Similarly, growth-associated protein 43 (Gap43), which has long been associated with regenerating axons, can also promote neurite outgrowth, but not through an inhibitory environment 98,99 . In transgenic mice that overexpress Gap43, together with a similar protein Cap23, lesioned dorsal column axons will spontaneously regenerate into a peripheral nerve graft in the absence of a peripheral conditioning lesion 100 . However, the ability of…”
Section: Future Perspectivesmentioning
confidence: 99%
“…But which genes are sufficient, and which are necessary? Using a candidate gene approach, Skene and colleagues recently showed that overexpressing two growth cone proteins, GAP-43 and CAP-23, is sufficient to dramatically increase DRG axon growth in vitro and in the injured spinal cord in vivo (Bomze et al 2001). Experiments are underway to characterize the differences in axon growth between developing and regenerating sensory neurons.…”
Section: Do Pns Neurons Lose Their Intrinsic Axon Growth Ability?mentioning
confidence: 99%